Pre-clinical models to define correlates of protection for SARS-CoV-2 - Brady, Caolann; Tipton, Tom; Longet, Stephanie; Carroll, Miles W. (Frontiers in Immunology, 2023)
A defined immune profile that predicts protection against a pathogen-of-interest, is referred to as a correlate of protection (CoP). A validated SARS-CoV-2 CoP has yet to be defined, however considerable insights have been provided by pre-clinical vaccine and animal rechallenge studies which have fewer associated limitations than equivalent studies in human vaccinees or convalescents, respectively. This literature review focuses on the advantages of the use of animal models for the definition of CoPs, with particular attention on their application in the search for SARS-CoV-2 CoPs. We address the conditions and interventions required for the identification and validation of a CoP, which are often only made possible with the use of appropriate in vivo models.